Edukasi Penggunaan Komposit Polimer ABS / Nanopartikel Untuk Meningkatkan Spesifikasi Pada Salah Satu Produk Komponen Mobil Core Tray - Andi Rusnaenah; Isma Wulansari; Nur Azizah Kurniasari (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Nanocomposite polymers have become a major topic of research in nanotechnology. Nanoclays nanocomposite technology be able to improve the mechanical, thermal, and barrier performance properties with a minimum addition of <10 wt%. The deficiency of acrylonitrile butadiene styrene (ABS) component materials is flammability, so a method needed to increase ABS thermal which is through the synthesis of ABS nanocomposite by mixing graphene, nitrile butadiene rubber (NBR) and montmorillonite nanofil 15 (N15) in ABS mixture. The core tray has low heat resistance, is easily damaged and understands composite processes that can improve the thermal properties of the materials used. This program focuses on helping to improve industrial knowledge in solving the problem of processing raw materials used to produce core trays. Nanoparticles can provide the industry with an understanding of the application of nanoparticles to ABS materials. Data obtained that get an increase in the knowledge, skills and income of partners. The conclusion is necessary to monitor the application of nanocomposites by mixing the raw materials for making nanoparticles with graphene, NBR and N15 in a mixture of ABS, conducting increased research in plastic materials to improve quality and impact on competitive prices, establishing partnerships to product improvement with conducting research and product testing.